STUDI PERUBAHAN LUASAN HUTAN MANGROVE DI DUSUN PINTAU DESA TANJUNG SATAI KECAMATAN PULAU MAYA KABUPATEN KAYONG UTARA - A, Burhanudin; Thamrin, Eddy; Idham, M (Universitas Tanjungpura, 2017)
This research focus to examine changing mangrove area during 5 years and their relationship with perception of Dusun Pintau people. Raster and vector data were used in this research. Raster data is processed by georeferencing and geoprocessing. Other that, purposive sampling was used to determine number of respondents. From vector data is known that mangrove area constant at 58.58 Ha in 5 years, this mean, it area didn’t change. From raster data, it area was changed which are 16.3 Ha in 2012, 18.52 Ha in 2013, 18.89 Ha in 2014, and 18.9 Ha in 2015.Base on terestris data, also reveal changed 18.8 Ha in 5 years. From correspondency activity reveal that mangrove area is 12 Ha. People’s perception to mangrove area change is different depend on age, education background, and cosmopolitan level. 66.7% young people have positive perception, adult people who have positive perception is 50%, and mature people generally (60%) have positive perception. Base on education background, 58% of elementary school alumna, 46% junior school alumna, and 81.18% senior school alumna have positive perception. Base on this study, mangrove forest area in Dusun Pintau has change. It area was decrease 0.58 Ha/year. This degradation was caused by fish and shrimp farm construction during five year. Keywords: Dusun Pintau, Mangrove, Raster, Sikap Masyarakat, Vektor